Lanaw S'Bu - Pregonir, Adrian Medina (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
Lanaw S’bu is a poetry collection that celebrates the cultural heritage, folktales, and myths of the Tboli, an ethnolinguistic group from the southern Philippines. The collection features poems that explore the deep connection between the Tboli people and their natural environment, while also delving into their unique worldviews and beliefs. With themes ranging from the creation of the world to the daily rituals and customs of the Tboli people, Lanaw S’bu highlights the importance of storytelling and oral tradition in preserving cultural heritage.